PELATIHAN LITERASI STATISTIK BERBASIS HOTS DI SMA NEGERI 8 KOTA BENGKULU - Dyah Setyo Rini; Pepi Novianti; Idhia Sriliana (Jurnal Berdaya Mandiri, 2020)
The era of the industrial revolution 4.0 or the era of disruption requires new literacy which includes data literacy, technological literacy and human literacy. HOTS-based statistical literacy training at SMA Negeri 8 Bengkulu City aims to foster and guide Class XII students in understanding and analyzing HOTS-based statistical literacy. The method used to achieve these objectives is coaching and training. The results obtained based on this activity are the coaching and training conducted that gives positive results and significantly influences students' knowledge and abilities regarding Statistics Literacy. In addition, students get an overview of statistical data understanding that is very important and continues to grow in the revolutionary 4.0 era.